2011
DOI: 10.1039/c1mt00025j
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic evidence of unaccounted for Fe and Cu erythropoietic pathways

Abstract: Despite its potential importance for understanding perturbations in the Fe-Cu homeostatic pathways, the natural isotopic variability of these metals in the human body remains unexplored. We measured the Fe, Cu, and Zn isotope compositions of total blood, serum, and red blood cells of ~50 young blood donors by multiple-collector ICP-MS after separation and purification by anion exchange chromatography. Zinc shows much less overall isotopic variability than Fe and Cu, which indicates that isotope fractionation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
153
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(165 citation statements)
references
References 38 publications
(40 reference statements)
10
153
2
Order By: Relevance
“…Hence, redox processes play the decisive role in iron isotope fractionation between compartments of the human body, regardless of whether the pathways are direct or indirect. 1,13 Conclusions A chemical separation procedure using microwave treatment and anion exchange chromatography was developed for analysis of iron isotopes in human blood plasma by MC-ICP-MS. The isotope composition of plasma is exceedingly sensitive to hemolysis which may occur during blood sampling and subsequent centrifugation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, redox processes play the decisive role in iron isotope fractionation between compartments of the human body, regardless of whether the pathways are direct or indirect. 1,13 Conclusions A chemical separation procedure using microwave treatment and anion exchange chromatography was developed for analysis of iron isotopes in human blood plasma by MC-ICP-MS. The isotope composition of plasma is exceedingly sensitive to hemolysis which may occur during blood sampling and subsequent centrifugation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one study has reported the iron composition of human blood plasma and found it to be enriched in 56 Fe over 54 Fe relative to blood, and hence being of composition closer to liver iron. 13 In this study we test these hypotheses by presenting precise iron stable isotope ratios measured in human erythrocytes and plasma samples. Blood was sampled over a period of 21 days from 12 healthy male adults.…”
Section: Introductionmentioning
confidence: 99%
“…Cu ratio, expressed in delta units (Method), varies between organs from −1‰ in liver to +1‰ in kidney (6) (for comparison, this ratio ranges from −3‰ to +2.5‰ in terrestrial materials). In humans, the 65 Cu/ 63 Cu ratio in blood and bone differs between men and women (7,8), partly because a sizeable proportion of the women's blood copper comes from the liver to balance menstrual losses (9,10). The body 65 Cu/ 63 Cu ratio varies according to that of diet (11) and also seems to be age dependent (12).…”
mentioning
confidence: 99%
“…10 % for non-heme iron 1 . To take this effect into account, we weigh the mean diets isotope composition by these efficiencies and the iron consumption ( 4 an average δ 56 Fe of -2.74 ± 0.16 ‰ for 22 males and -2.57 ± 0.19 ‰ for 25 females. The average of all samples from these three studies is -2.76 ± 0.18 ‰ for males and -2.50 ± 0.20 ‰ for females from which we obtained a fractionation factor for intestinal absorption of -1.3 ‰ for female omnivores and -2.0 ‰ for female vegetarians.…”
Section: Resultsmentioning
confidence: 99%